Viabilidad de la incorporación de las bicicletas y ciclorutas dentro de un sistema de transporte regional en un contrato plan (2018)
Given the needs of displacements that are requiring dynamically in the area between the municipalities of Mosquera, Funza, Madrid and Bogota D.C., due to the different job offers presented on this industrial corridor, commercial and residential, this degree project aims to analyze the viability of a system of regional interconnection between the municipalities mentioned above, through corridors of cycle routes, whose alternative designs involve the territory environment and adapt to climate change.